Pengaruh Kepercayaan Merek Dan Citra Merek Terhadap Loyalitas Merek Indomie - James Rianto Situmorang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
popular of them is the Indomie. Indomie’s brand is very popular in Indonesia which shows that Indomie has a good brand trust and brand image in the minds of customers. Indomie also has very loyal customers who have consumed Indomie for years. This shows that Indomie's brand loyalty has also been embedded in the hearts of customers. Therefore, this study aims to determine the effect of brand trust and brand image on Indomie's brand loyalty. A total of 300 people comprised of 75 consumers that buy instant noodles from four supermarkets in Bandung were selected as participants. The T-test results proposed hypotheses 1 and 2 that brand trust and image significantly affect Indomie's loyalty. Also, the F-test proposed hypothesis 3 that brand trust and brand image simultaneously influence Indomie’s brand loyalty by 53.2%. The linear regression equation as Y = 1.577 + 0.282 X1 + 0.385 X2 showed brand image coefficient is greater than brand trust. This indicates that Indomie is the most popular of all the instant noodles in Indonesia. Keywords: Brand Image, Brand Loyalty, Brand Trust